2021
DOI: 10.1097/mpg.0000000000003289
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Tolerance of a Novel Anti‐Regurgitation Formula

Abstract: Objectives: A novel anti-regurgitation (AR) formula has been designed to support gut health and improve gastrointestinal (GI) symptoms beyond regurgitation. This study assessed the tolerance and safety of this new AR formula. Methods: This was a 4-week double-blind, randomized, controlled trial with a 4-week extension in formula-fed infants with regurgitation. The new AR (Test) formula contained 0.4 g/100 mL locust bean gum (LBG) as thickener, partly fermented formula w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 44 publications
(67 reference statements)
0
14
0
Order By: Relevance
“…The gastric emptying of a pHF-W is comparable to that of mother's milk and significantly faster than that of intact milk protein [56] L. reuteri was shown to reduce regurgitation and to enhance gastric emptying [57]. Different studies showed a significant effect on regurgitation within one week of dietary treatment [58][59][60].…”
Section: Regurgitation: Phf Probiotics and Starchmentioning
confidence: 99%
“…The gastric emptying of a pHF-W is comparable to that of mother's milk and significantly faster than that of intact milk protein [56] L. reuteri was shown to reduce regurgitation and to enhance gastric emptying [57]. Different studies showed a significant effect on regurgitation within one week of dietary treatment [58][59][60].…”
Section: Regurgitation: Phf Probiotics and Starchmentioning
confidence: 99%
“…This percentage was the same as before the intervention started [30]. The recent trial comparing LBG thickened formula with and without FOS and GOS (and postbiotics) showed no difference in efficacy [11 ▪▪ ].…”
Section: Prebioticsmentioning
confidence: 67%
“…The efficacy of the standard and new antiregurgitation formula, both thickened with LBG was in the overall group comparable within the first week of intervention [11 ▪▪ ]. Post-hoc analyses suggest that the novel formula may result in more improvement of the gastrointestinal symptom burden in infants with more severe symptoms [11 ▪▪ ].…”
Section: Thickened Formulamentioning
confidence: 91%
See 1 more Smart Citation
“…Figure 1 is a flow diagram of the identification of eligible trials. In addition to 5 randomized controlled trials (RCTs) identified earlier in our 2015 systematic review (5–9), 6 new RCTs were identified (10–15) (Table 1). Characteristics of the excluded studies are summarized in Table 3, Supplementary Digital Content, http://links.lww.com/MPG/C753 .…”
Section: Resultsmentioning
confidence: 99%